Penguatan Skill Listening dan Vocabulary di MTs Terpadu Berkah Palangka Raya melalui lagu One Call Away oleh Charlie Puth - Alya Audria; Ayu Sundari; Fatma Fatma; Rizki Hasanah; Mayra Musdalifah; Siti Rahmawati; Kholida Ziya; Abdul Syahid (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This article examines community service efforts aimed at strengthening listening skills and expanding vocabulary among students at MTs Integrated Berkah Palangka Raya through an innovative approach using Charlie Puth's song "One Call Away." The activities include the introduction of song lyrics, listening exercises, and writing exercises based on the heard lyrics. The research aims to enhance students' English language comprehension profoundly. The outcomes of these activities are expected to positively contribute to the development of language skills in the educational environment.